Engineering and Applied Sciences: Assessment of Research Skills in First-Semester Students (Innovation & Development in Engineering and Applied Science, 2024)
The technological and scientific development of society heavily relies on the education of engineers in sciences, where skills become crucial in addressing the inherent challenges of this field. The present study aimed to determine the level of research skills among first-semester students in engineering and science disciplines at an Ecuadorian university. The research conducted was non-experimental and cross-sectional. The approach is quantitative and descriptive in its scope, involving 163 students. Results revealed that over 50% of students consistently perceived these skills as "almost always" and "always" based on a Likert scale with five levels of assessment. This reflects a positive perception; however, a weakness was identified in the analytical and interpretative domain. Considering this data is from an early stage of education, this finding is deemed acceptable.
Keywords: universitary education; research skills; applied science